Dominant Factors Contributing to Anxiety in Triage Yellow Patients in the Emergency Department of Ciremai General Hospital: A Quantitative Multivariate Approach - Kasmad, Kasmad (Poltekkes Kemenkes Palu, 2025)
Triage is a critical process in prioritizing patient care, particularly for P2 (yellow label) patients in the emergency department who are at risk of clinical deterioration. This study aimed to quantitatively and multivariately analyze the factors influencing anxiety levels among P2 triage patients at the Emergency Department of RSU Ciremai. This analytical quantitative study employed a cross-sectional design. A total of 96 P2 triage patients were selected using purposive sampling. The variables examined included response time, therapeutic communication, and family support. Data were analyzed using chi-square tests for bivariate analysis and multiple logistic regression for multivariate analysis. Bivariate analysis revealed significant associations between anxiety levels and response time (p = 0.002), therapeutic communication (p = 0.001), and family support (p = 0.004). Multivariate analysis showed that delayed response time (OR = 3.46; 95% CI: 1.52–7.89), ineffective therapeutic communication (OR = 4.20; 95% CI: 1.85–9.52), and low family support (OR = 3.10; 95% CI: 1.38–6.95) significantly increased the risk of severe anxiety. Among these factors, ineffective therapeutic communication emerged as the most dominant, with the highest odds ratio. Response time, therapeutic communication quality, and family support are key factors associated with anxiety in P2 triage patients. Emergency nursing interventions should focus on enhancing communication skills through targeted staff training, implementing rapid response protocols to reduce delays, and actively involving family members in the care process to help reduce patient anxiety and improve psychological outcomes.